Chaplaincy Institute in Ukraine and EU countries - Kryvenko, Iuliia; Omelchuk, Oleksandr; Chernovaliuk, Iuliia (Journal of Education Culture and Society, 2020)
Aim. The aim of the article is devoted to the research of chaplaincy institutes in Ukraine, taking into account the experience of EU countries. Concept. During the study determined, that the interaction between military service and religion is based on a universal socio-cultural tradition, has a complex, multi-level structure, covering the whole socio-institutional level (society - social institutions - social organizations of the individual) and leads to the creation of a specific social structure - military-religious institute the institute of military chaplaincy. Conclusions. It is found that there are no historical analogies in the world for the creation of a military chaplaincy institute under such conditions, which makes the present Ukraine experience unique, but to this day the issue of state regulation in the field of pastoral care of military personnel of the Armed Forces of Ukraine and the creation of a military chaplaincy institute remains unregulated. In contrast to Ukraine, the legal support for the existence of an institute of military chaplaincy in Poland is provided by the relevant state normative-legal acts and by-church documents. Most European countries have the opportunity to serve for both military and civilian chaplains. Due to the analysis of legal acts and experience of European countries it should be determined that Ukraine chooses the "European" model of chaplaincy. The article also identifies the positive aspects of the organizational experience of military chaplaincy as to possible borrowing for Ukraine. The notion of a chaplain-volunteer is typical of Ukrainian legislation.